2020
DOI: 10.1038/s41559-020-1124-7
|View full text |Cite
|
Sign up to set email alerts
|

Dissimilation of synonymous codon usage bias in virus–host coevolution due to translational selection

Abstract: Data availability For the yeast Ribo-Seq data underlying Fig. 1, all accession numbers for publicly available datasets were listed in Supplementary Table 1. For the human Ribo-Seq data underlying Fig. 2, the original dataset is available from NCBI SRA under accession number SRR3623932 and SRR3623937. The raw data underlying Fig. 3 is shown in Supplementary Figure 6 and Supplementary Table 3. The species identified as virus or its natural/symptomatic hosts were listed in Supplementary Table 5, with their genomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
104
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(113 citation statements)
references
References 69 publications
9
104
0
Order By: Relevance
“…The consumption of specific tRNAs for the virus replication could thus be an alternative to controlling host protein synthesis machinery as well as generating deleterious collateral effects on the function of the host cells. Recent evidence supports the idea that high codon usage similarity between virus and host can lead to a deleterious effect on the host (Chen et al, 2020). Furthermore, Chen et al (2020) have shown that codon composition of highly expressed viral genes regulates the tRNA availability, affecting the decoding time of codons in the infected cells.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…The consumption of specific tRNAs for the virus replication could thus be an alternative to controlling host protein synthesis machinery as well as generating deleterious collateral effects on the function of the host cells. Recent evidence supports the idea that high codon usage similarity between virus and host can lead to a deleterious effect on the host (Chen et al, 2020). Furthermore, Chen et al (2020) have shown that codon composition of highly expressed viral genes regulates the tRNA availability, affecting the decoding time of codons in the infected cells.…”
Section: Introductionmentioning
confidence: 77%
“…Recent evidence supports the idea that high codon usage similarity between virus and host can lead to a deleterious effect on the host (Chen et al, 2020). Furthermore, Chen et al (2020) have shown that codon composition of highly expressed viral genes regulates the tRNA availability, affecting the decoding time of codons in the infected cells. In this manner the viral infection can convert abundant codons into scarce codons, reshaping the human codon optimality pattern.…”
Section: Introductionmentioning
confidence: 77%
“…because having codon usage similar to their host would allow them to replicate faster due to better translation efficiency of their mRNA(s) 11 . However, it is worth noting that viral codon usage often does not closely resemble the codon usage of their hosts 12,13 , a phenomenon that is not well understood.…”
mentioning
confidence: 99%
“…On the other hand, given the similarity of SARS-CoV-2 SDA with the phylogenetically closest bat coronavirus, it seems that a translational selection to increase SDA would have acted before the putative zoonosis from bats or other intermediate hosts. Furthermore, in agreement with the highest translational potential of SARS-CoV-2 in their target tissues, a recent model of viral tropism suggested that a tradeoff exists between the efficiency of viral translation and the translational load on the host, indicating that an improved codon usage can make the difference between symptomatic and natural hosts 51 .…”
Section: Discussionmentioning
confidence: 60%